2001
DOI: 10.4141/a01-033
|View full text |Cite
|
Sign up to set email alerts
|

Repeated injections with dexamethasone in healthy lactating sows and the effect on growth rate of their suckling piglets

Abstract: K. 2001. Repeated injections with dexamethasone in healthy lactating sows and the effect on growth rate of their suckling piglets. Can. J. Anim. 81: 593-596. Twelve lactating sows were given two doses of 14 mg of dexamethasone and 12 controls were given two doses (7.0 mL) of physiological saline. During the treatment period, total litter weight gain in litters of dexamethasone-treated sows was significantly less (P = 0.02) than weight gain of control litters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…As for the IM administration of both dexamethasone and vitamin E/Se combination in our study at the first 3 days of life, the use of dexamethasone could improve the growth of LBW piglets due to its beneficial effects on their digestive capability, metabolism, and reaction to stress [ 29 , 33 , 51 ]. In a recent study, it was reported that the use of dexamethasone in piglets infected by highly pathogenic PRRSV (HP-PRRSV) increases the disease severity and should be avoided in the clinical treatment of HP-PRRS [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the IM administration of both dexamethasone and vitamin E/Se combination in our study at the first 3 days of life, the use of dexamethasone could improve the growth of LBW piglets due to its beneficial effects on their digestive capability, metabolism, and reaction to stress [ 29 , 33 , 51 ]. In a recent study, it was reported that the use of dexamethasone in piglets infected by highly pathogenic PRRSV (HP-PRRSV) increases the disease severity and should be avoided in the clinical treatment of HP-PRRS [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids play an important role in intestinal maturation and function [ 29 ], in the regulation of prenatal and postnatal growth [ 30 ], metabolism [ 31 ], and homeostasis [ 32 ]. Furthermore, studies suggest that the surge in glucocorticoids, which are related to the natural birth process, is a significant mediator of postnatal development and growth in viviparous animals [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prolactin, glucocorticoids, and insulin are necessary for inducing milk protein synthesis in mammary explant culture studies in rats (Bolander et al, 1981;Kulski et al, 1983), and administration of GH increases milk yield in dairy cows (Bauman, 1999;Yang et al, 2005). In contrast, treatment of sows with any of these hormones does not improve milk synthesis or litter growth during lactation, and the reasons are unknown (Farmer et al, 1999;Norby et al, 2001). Hormone activity in the porcine mammary gland may depend on the availability of hormone receptors, which is partially controlled by their transcription rates (Alberts et al, 2008).…”
Section: Introductionmentioning
confidence: 99%